2013
DOI: 10.1097/qad.0b013e328363bf56
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of brief screening tools for neurocognitive impairment in HIV/AIDS

Abstract: Objective(s):To systematically review literature on brief screening tools used to detect and differentiate between normal cognition and neurocognitive impairment and HIV-associated neurocognitive disorders (HANDs) in adult populations of persons with HIV.Design:A formal systematic review.Methods:We searched six electronic databases in 2011 and contacted experts to identify relevant studies published through May 2012. We selected empirical studies that focused on evaluating brief screening tools (<20 min) for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
77
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 62 publications
(40 reference statements)
8
77
2
3
Order By: Relevance
“…Additionally, this study did not include individuals with HAD. As one previous meta-analytic study (Zipursky et al, 2013) suggested that the HDS and IHDS were sensitive in screening for more severe forms of HAND, such as HIV-associated dementia, and were less sensitive to milder forms of HAND, our findings may be stem from these previously reported finding, as our study did not support inclusion of individuals with HAD. Recruiting individuals with HAD would have proven difficult, given our study required all individuals to complete a comprehensive neuropsychological assessment.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Additionally, this study did not include individuals with HAD. As one previous meta-analytic study (Zipursky et al, 2013) suggested that the HDS and IHDS were sensitive in screening for more severe forms of HAND, such as HIV-associated dementia, and were less sensitive to milder forms of HAND, our findings may be stem from these previously reported finding, as our study did not support inclusion of individuals with HAD. Recruiting individuals with HAD would have proven difficult, given our study required all individuals to complete a comprehensive neuropsychological assessment.…”
Section: Discussioncontrasting
confidence: 67%
“…One recent meta-analytic study reviewing the HDS and IHDS demonstrated that the HDS has poor pooled sensitivity and the IHDS had moderate pooled sensitivity in detecting a range of cognitive impairment; the authors of this study noted that while the HDS and IHDS performed well to screen for HAD, they were less sensitive to milder HAND conditions (Zipursky et al, 2013). Another systematic review (Haddow, Floyd, Copas, & Gilson, 2013) examining the screening accuracy of the HDS and IHDS reported that both scales were low in predictive accuracy.…”
mentioning
confidence: 89%
“…[89][90][91][92] It is clear from the pooled estimates that the sensitivity of the scale is low and the specificity is only slightly better, while differences in methodology and study selection have led to heterogeneous estimates between meta-analyses and individual studies. The HDS is designed to be highly standardized, so heterogeneity is more likely to result from the diverse range of testing batteries, case definitions, and diagnostic thresholds used in the "gold standard".…”
mentioning
confidence: 99%
“…Other short batteries include the neurocognitive HIV study screen, 115 the brief neurocognitive screen, 29 the NeuroScreen, 116 the high sensitivity cognitive screen, 117 and multiple other short combinations of standardized tests, which have been reviewed systematically in two publications. 90,92 Computerized tools, such as Cogstate and CalCAP, may be used as screening instruments or as more detailed batteries. 9,118,119 Despite widespread use in clinical research, computerized assessment is infrequently encountered in routine practice.…”
Section: Short Neuropsychological Testing Batteries Used As Screeningmentioning
confidence: 99%
“…Development of screening instruments that are as sensitive and specific as the International HIV Dementia Scale (also known as the Sacktor test ) are urgent. These can be used in less than 20 minutes and have the capacity to detect all clinical forms of HAND [811]. …”
mentioning
confidence: 99%